Family context as a double-edged sword for psychological distress amid the COVID-19 pandemic with the mediating effect of individual fear and the moderating effect of household income - Chen, Bowen; Gong, Weijie; Lai, Agnes Yuen Kwan; Sit, Shirley Man Man; Ho, Sai Yin; Yu, Nancy Xiaonan; Wang, Man Ping; Lam, Tai Hing (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic drives psychological distress. Previous studies have mostly focused on individual determinants but overlooked family factors. The present study aimed to examine the associations of individual and family factors with psychological distress, and the mediating effect of individual fear and the moderating role of household income on the above associations. Methods We conducted a population-based cross-sectional survey on Chinese adults in Hong Kong from February to March 2021 (N = 2,251) to measure the independent variables of anti-epidemic fatigue, anti-epidemic confidence, individual and family members’ fear of COVID-19, and family well-being (range 0–10), and the dependent variable of psychological distress (through four-item Patient Health Questionnaire, range 0–4). Results Hierarchical regression showed that anti-epidemic fatigue was positively (β = 0.23, 95% CI [0.18, 0.28]) while anti-epidemic confidence was negatively (β = −0.29, 95% CI [−0.36, −0.22]) associated with psychological distress. Family members’ fear of COVID-19 was positively (β = 0.11, 95% CI [0.05, 0.16]) while family well-being was negatively (β = −0.57, 95% CI [−0.63, −0.51]) associated with psychological distress. Structural equation model showed that individual fear mediated the above associations except for family well-being. Multi-group analyses showed a non-significant direct effect of anti-epidemic confidence and a slightly stronger direct effect of family well-being on psychological distress among participants with lower incomes, compared to those with higher incomes. Conclusion We have first reported the double-edged effect of family context on psychological distress, with the positive association between family members’ fear of COVID-19 and psychological distress fully mediated by individual fear and the negative association between family well-being and psychological distress moderated by income level. Future studies are warranted to investigate how the contagion of fear develops in the family and how the inequality of family resources impacts family members’ mental health amid the pandemic.